Discrimination of structural isomers of amphetamine using carbon dioxide negative-ion chemical ionization mass spectrometry. Issue 2 (1997) - Thurbide Thurbide, Kevin B. Kevin B.; Elson Elson, C. M. C. M.; Sim Sim, P. G. P. G.
Abstract : The negative‒ion chemical ionization mass spectra of a group of structural isomers of amphetamine have been studied using carbon dioxide as the reagent gas. Characteristic and reproducible differences are observed for each member of the set implying that this technique offers a means of distinguishing among groups of amphetamine isomers. Characteristic adducts to the molecular ion are observed in the form (M–[H]+[O]) and (M–[H]+[CO2 ]). Descriptions of some fragments are given based on the mass spectral behaviour of a set of analogue compounds and the results of oxygen-18 labelled carbon dioxide reagent gas experiments. Contents of the carbon dioxide plasma and their impact on various analytes is also discussed.